Home Stays for the Development of Tourism in Thrissur District - Helna K Paul (POST GRADUATE DEPARTMENT OF COMMERCE AND MANAGEMENT STUDIES SRI C ACHUTHA MENON GOVERNMENT COLLEGE, THRISSUR, KERALA, 2013)
Hospitality has always been one of the most valued service areas of Indian culture in general and Kerala, in particular. Hospitality becomes more homely when the guests stay at home and this belief was utilized to the full by the Keralites as Kerala was one of the first states in India to initiate and develop the concept of homestays. In a homestay, the tourist lives with the family for some part of his or her journey and enjoy the culture and tradition of the land. Even though homestay is regarded as a home away from sweet home, tourist stay in hotels by paying high rates for rooms. This makes some kind of problems for the homestay providers because for some it’s the only livelihood. By conducting census method of data collection through telephone interview, study concludes about different problems of homestay owners and suggests some solution